PENGARUH FINANCIAL DISTRESS, FIRM SIZE, LIKUIDITAS, DAN PRICE TO CASH FLOW FROM OPERATING ACTIVITIES TERHADAP RETURN SAHAM - Nurhalimah Nurhalimah (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2024)
Stock returns are generated by investors from buying and selling activities of the stocks they own. The generated return is determined by the increase or decrease in the stock prices. These prices are formed by the fundamental performance of the company. The purpose of this research is to examine the influence of factors such as financial distress, firm size, liquidity, and price to cash flow from operating activities on stock return. This study was conducted on transportation and logistics companies during the period of 2019-2022. A total of 22 companies were selected as samples for this research, using purposive sampling method and obtaining 88 relevant research data. The relationship between the dependent variable and independent variables was analyzed using multiple linear regression. The hypothesis test showed that the variable of financial distress, analyzed using the Zmijewski method, did not have any significant influence on stock return. Firm size, measured by total assets, was also not found to have a significant impact on stock return. The analysis of liquidity using the current ratio did not find a significant influence on stock return. However, price to cash flow from operating activities showed a significant and positive influence on stock return. This factor can be taken into consideration by investors and potential investors when analyzing the financial fundamentals of transportation and logistics companies before investing, as it has an impact on stock return.